China-EU trade relations: Is China an economic partner, competitor or rival? - Bahri Yılmaz (Koç University-TÜSIAD Economic Research Forum (ERF), 2020)
China's expansionary economic policy toward Western countries was not predicted only in Washington but also in the EU. As expected, the EU became aware of the fact that China is a tough competitor, redesigning not only the world economy but also challenging Europe under the 17+1 and the Belt and Road Initiative. In this paper, first attempt will be made to examine the EU's trade relations with China. Then, it will be discussed the main economic issues and disputes between the EU and China. We will ask the following questions: Why is China important for the EU, and why is the EU important for China? What about the EU Strategy on China? What are the trade priorities for the EU and China? How can the EU counter unfair competition from China? What are the EU's and China's plans to connect with each other across the continent? Is China welcome in Europe? What are the advantages of the Member States in the EU working together vis-à-vis China?
Keywords: 330; Internationale Wirtschaftsbeziehungen; Internationaler Wettbewerb; Handelskonflikt; EU-Staaten; China